2016
DOI: 10.14569/ijacsa.2016.071228
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach to Conceptual Modeling

Abstract: Abstract-Conceptual modeling is supporting understanding and communication of the requirements in developing the information system (IS). The nature of requirements is usually divided into the functional (FRs) and non-functional requirements (NFRs). Thus, the scholars who are representing the conceptual modeling separate FRs and NFRs. Attempting to create an integrated framework for conceptual modeling of FRs and NFRs a new approach is being represented. In order to justify the approach, the research work and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In 2016, [27] introduced a new integrated framework that merges the functional and non-functional requirements in developing an information system. The following algorithm of the proposed integrated system for computational modeling is an outcome of the literature review, study gaps identified, and work experience identified.…”
Section: Integrated Framework For Conceptual Modelmentioning
confidence: 99%
“…In 2016, [27] introduced a new integrated framework that merges the functional and non-functional requirements in developing an information system. The following algorithm of the proposed integrated system for computational modeling is an outcome of the literature review, study gaps identified, and work experience identified.…”
Section: Integrated Framework For Conceptual Modelmentioning
confidence: 99%